A socio-historical perspective on the Amazigh (Berber) Cultural Movement in North Africa0 - El Aissati, Abderrahman (Afrika Focus, 2005)
North Africa has known various colonizations which in contact with indigenous ones have given the area a special character. One continuing presence since antiquity is that of the Berbers, or the Imazighen, the indigenous population of the area. In this article an attempt is made to shed light on the status of the language and culture of the Imazighen, and in particular on the recent calls for official recognition of the Amazigh language in the constitutions of the two countries with the highest presence of Imazighen, namely Morocco and Algeria. Although some recent developments, like the teaching of the Amazigh language in primary schools, give reason enough to be optimistic about the future of the indigenous language and culture, a closer look at the ideological background of pan Arab-nationalists casts doubts on any serious government intentions to guarantee the maintenance and development of the Amazigh language and culture. This ideology will be brought to light by contrasting the constitutional rights that some Muslim and/or African countries grant to their citizens who speak different languages than the official one(s). Key words: Amazigh identity, Amazigh Language, Berber, culture, linguistic rights, minority languages, pan-Arabism